(untitled) (Ustozlar uchun, 2026)
This study explores the role of the English language in international communication. It examines how English has become a global lingua franca and its importance in various fields such as business, education, science, and technology. The research highlights the factors contributing to the global spread of English and analyzes its impact on intercultural communication. Particular attention is given to the advantages and challenges of using English as a common language among speakers of different linguistic and cultural backgrounds. The study demonstrates that English plays a crucial role in facilitating global interaction, promoting cooperation, and ensuring effective communication in the modern world.